1947
DOI: 10.1515/zna-1947-0310
|View full text |Cite
|
Sign up to set email alerts
|

Kristallchemie des In und Ga in Legierungen mit einigen Übergangselementen (Ni, Pd, Pt, Cu, Ag und Au)

Abstract: HermannBraune zum 60. Geburtstag gewidmet Zur Erweiterung der Kenntnis über das chemische Verhalten des Galliums und Indiums in Legierungen wurde eine größere Anzahl bislang unbekannter (20) Kristallstrukturen intermetallischer Phasen dieser Elemente mit Übergangselementen bestimmt. Unter den gefundenen Typen sind solche bevorzugt, die vom geometrischen Standpunkt aus (wegen der atomaren Abstandsverhältnisse) das Wirken heteropolarer Kräfte erkennen lassen. Die Ergebnisse bestätigen die Annahme heteropolarer B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
1
1

Year Published

1949
1949
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(36 citation statements)
references
References 0 publications
1
28
1
1
Order By: Relevance
“…This phase had first been reported by Hellner and Laves [11], who labeled the crystal structure ''g-brass type with vacancies''. Later Hellner confirmed the existence of Ga 4 Ni [12].…”
Section: Ga-rich Part Of the Phase Diagrammentioning
confidence: 62%
See 1 more Smart Citation
“…This phase had first been reported by Hellner and Laves [11], who labeled the crystal structure ''g-brass type with vacancies''. Later Hellner confirmed the existence of Ga 4 Ni [12].…”
Section: Ga-rich Part Of the Phase Diagrammentioning
confidence: 62%
“…The most recent experimental study of the Ga-Ni phase diagram was carried out by Ducher et al [5], who clarified a number of uncertainties which were present in the literature [8,[11][12][13][14][15][16][17][18][19][20][21][22] on which the phase diagram compilation by Lee and Nash [23] was based.…”
Section: General Phase Diagrammentioning
confidence: 99%
“…The latter is relatively large with a maximum x Ga Z0.14 at 1634 K. Eight intermetallic compounds Ga 6 Pt, Ga 7 Pt 3 , Ga 2 Pt, Ga 3 Pt 2 , GaPt, Ga 3 Pt 5, GaPt 2 , and GaPt 3 were found in the Ga-Pt system, in which GaPt and GaPt 3 melt congruently and others are formed by peritectic reactions. The crystal structures of all these compounds were measured by Bhan and Schubert [9], Schubert et al [10], Zintl et al [11], Swenson and Morosin [12], Hellner and Laves [13], and Chattopadhyay and Schubert [14] respectively. Oya [15] revised Pt-rich portion of the Pt-Ga phase diagram by metallography, X-ray analysis and DTA.…”
Section: Experimental Phase Diagram Datamentioning
confidence: 99%
“…26 The authors 20 concluded that the phase composition of 'PdIn 3 ' (25at.%Pd) must be corrected to Pd 3 In 7 (30at.%Pd). This is in agreement with experimental and calculated XRD spectra from the atomic positions with the freeware software PowderCell in this work and a corresponding study in bulk Pd-In samples.…”
Section: Pd-in Phase Diagrammentioning
confidence: 99%
“…The measured remelting temperatures of Pd/In thin films in this work were in reasonable agreement with the reported decomposition temperatures of 'PdIn 3 ' and Pd 2 In 3 . 27 Based on the data from literature 12,20,26,27 and of this work, a revised partial Pd-In phase diagram was constructed and is given in Fig. 7b.…”
Section: Pd-in Phase Diagrammentioning
confidence: 99%